2018
DOI: 10.1044/2017_ajslp-17-0032
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intensive Speech Treatment on Conversational Intelligibility in Spanish Speakers With Parkinson's Disease

Abstract: These findings support the implementation of intensive voice treatment to improve conversational intelligibility in Spanish speakers with PD with dysarthria as well as to improve the speakers' perception of their daily communicative capabilities. Clinical and theoretical considerations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
1
23
0
2
Order By: Relevance
“…Studies have also looked at the longer-term effects of intervention using the VHI. [59][60][61]67 Moya-Galé et al, 61 using LSVT ® , reported a reduction in scores without significance 1 month post-treatment. Shih et al 67 reported a slight non-significant increase in scores (increased disability) 3 months post-treatment using group choral singing.…”
Section: Treatment Outcomes Relating To Proms and Patient Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also looked at the longer-term effects of intervention using the VHI. [59][60][61]67 Moya-Galé et al, 61 using LSVT ® , reported a reduction in scores without significance 1 month post-treatment. Shih et al 67 reported a slight non-significant increase in scores (increased disability) 3 months post-treatment using group choral singing.…”
Section: Treatment Outcomes Relating To Proms and Patient Perspectivesmentioning
confidence: 99%
“…Table 1 summarizes the findings of treatment studies (2008-2018) which incorporated a patient reported outcome measure (PROM) and/or sought to determine the perspective of pwPD of speech/voice and/or treatment. A range of PROMs including the VHI, [59][60][61][65][66][67]74 the V-RQOL,74 VAPP, 64 LSVT VAS, 59,60 and CETI-M 59,62 for spouse/ carers were used to determine the effects of treatment.…”
Section: Treatment Outcomes Relating To Proms and Patient Perspectivesmentioning
confidence: 99%
“…Benefits from increased vocal intensity in adult talkers have also been found in Spanish (Moya‐Galé et al . 2018), Mandarin (Lee and McCann 2009) and French (Sauvageau et al . 2015), among other languages.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, language‐specific responses to such treatment or cueing strategies are beginning to be documented (e.g., Moya‐Galé et al . 2016). Moreover, although French and English lexicons contain numerous cognates, the two prosodies differ considerably.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Spanish speakers with PD, Moya-Galé et al investigated the effects of LSVT LOUD on conversational intelligibility and self-perceptions of daily communicative capabilities. 77 Subjective and objective intelligibility measures (including the rigorous intelligibility measure of listeners' orthographic transcription accuracy) revealed substantial and significant gains in both variables post-treatment. These findings, therefore, support the implementation of this intensive treatment approach in Spanishspeaking populations and raise the question of whether vocal loudness increases conversational intelligibility universally.…”
Section: Crosslinguistic Research On Speech Treatment For Pdmentioning
confidence: 95%